Detection of oil spills based on gray level co-occurrence matrix and support vector machine - Li, Kai; Yu, Hongliang; Xu, Yiqun; Luo, Xiaoqing (Frontiers in Environmental Science, 2022)
Accurate reconnaissance of Marine oil spill is very important for emergency management of Marine oil spill accidents.Unmanned aerial vehicles (UAV) is a suitable carrier for offshore oil spill reconnaissance because of its fast deployment speed and low cost.Aiming at the identification accuracy of small oil spill accident in offshore port area and the problem of day and night reconnaissance,this study takes thermal infrared remote sensing images of oil leakage captured by UAV as the research object and proposes an oil spill detection method based on a Gray Level Co-occurrence Matrix (GLCM) and Support Vector Machine(SVM) method. Firstly, the extraction steps of image GLCM feature and the basic principle of SVM classification are studied. Then, the thermal infrared image data collected by UAV is preprocessed, including image filtering, clipping and rotation, and the sample database is generated. Subsequently, GLCM features of the samples were extracted, and the energy and correlation in GLCM were selected as classification features and sent to the SVM classifier to complete the oil spill detection of real-time thermal infrared images.The experimental results show that,compared with Classification and Regression Tree algorithm(CART) and Random Forests of Decision Trees(RF) algorithm, the detection accuracy of the method proposed in this paper reaches 95%, which were 10 and 2 percentage points higher than them respectively.The proposed method in this paper has fast recognition speed and high accuracy, and can provide all-weather recognition of oil spills for the detection of small oil spills in the offshore port area.